2020
DOI: 10.1088/1361-6463/abc6d5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of cold atmospheric plasma treatment, chemical versus physical strategy

Abstract: To date, reactive oxygen species and reactive nitrogen species have been regarded as the key factors causing the observable cellular death of cold atmospheric plasma (CAP)-treated cancer cells. The chemical basis of the conventional CAP treatment highlights apoptosis as the main CAP-triggered cell death mechanism. However, we recently demonstrated a strong anti-melanoma effect based on physically-based CAP treatment. In this study, we compared the anti-cancer effect of chemically-based versus physically-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 23 publications
(35 reference statements)
1
23
0
Order By: Relevance
“…Using a novel experimental design, it was found that melanoma cells B16F10 were effectively killed by physical factors mainly the EM effect from a typical CAP jet source [ 20 ]. Similar phenomena have also been observed later during the treatment on glioblastoma cells U87MG, lung cancer cells A549, bladder cancer cells MBT2, MB49, and breast carcinoma cells MDA-MB-231 [ 130 , 131 ]. In these cases, CAP treatment was performed on the bottom of an inverted cell culture dish or a multi-well plate.…”
Section: Necrosissupporting
confidence: 74%
“…Using a novel experimental design, it was found that melanoma cells B16F10 were effectively killed by physical factors mainly the EM effect from a typical CAP jet source [ 20 ]. Similar phenomena have also been observed later during the treatment on glioblastoma cells U87MG, lung cancer cells A549, bladder cancer cells MBT2, MB49, and breast carcinoma cells MDA-MB-231 [ 130 , 131 ]. In these cases, CAP treatment was performed on the bottom of an inverted cell culture dish or a multi-well plate.…”
Section: Necrosissupporting
confidence: 74%
“…Due to the surface tension, there was still a thin layer of medium to cover cells, particularly, at the junction between the wall and bottom of each well. Such an inverted setting for 10-20 min would not cause observable impact on the cell viability [16][17][18]. A single treatment was performed at the well "6D".…”
Section: Physically Based Cap Treatmentmentioning
confidence: 99%
“…Typically, CAP will generate at least three physical effects: thermal, ultraviolet (UV), and EM. Recently, we have demonstrated that EM effect rather than thermal and UV effects could trigger strong cell death in several cancer cell lines, including glioblastoma cells, lung cancer cells, as well as bladder cancer cells [16][17][18]. Such a physically triggered cell death is obvious necrosis, characterized by a fast cytosol aggregation and noticeable bubbling on the cellular membrane [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell death triggered by physical factors is characterized by cytosol aggregation and apparent bubbling on the cytoplasmic membrane, which is a process just lasting about 10 min. [144,145] Because the physically based CAP [140] (b) In situ H 2 O 2 measurement over 3 min Ar plasma jet treatment and 30 min after the treatment. Jurkat T cells and THP-1 cells were human monocytic cell lines, and the cancer cell lines were derived from an acute monocytic leukemia patient, respectively.…”
Section: The Selectivity Based On Physical Factorsmentioning
confidence: 99%